Feasibility and Acceptability of an Interactive Cancer-Communication Video Program Using African American Breast Cancer Survivor Stories. Issue 7 (2nd July 2020) - Pérez, Maria; Kreuter, Matthew W.; Yan, Yan; Thompson, Tess; Sefko, Julianne; Golla, Balaji; Margenthaler, Julie A.; Colditz, Graham; Jeffe, Donna B.
Abstract : To examine the feasibility and acceptability of an interactive video program of African American breast cancer survivor stories, we explored story reactions among African American women with newly diagnosed breast cancer and associations between patient factors and intervention use. During a randomized controlled trial, patients in the intervention arm completed a baseline/pre-intervention interview, received the video intervention, and completed a post-intervention 1-month follow-up interview. Additional video exposures and post-exposure interviews occurred at 6- and 12-month follow-ups. Multivariable linear mixed-effects models examined interview and clinical data in association with changes in minutes and actions using the program. After Exposure1, 104 of 108 patients allocated to the intervention reported moderate-to-high levels of positive emotional reactions to stories and identification with storytellers. Exposure1 mean usage was high (139 minutes) but declined over time ( p <.0001). Patients receiving surgery plus radiation logged about 50 more minutes and actions over 12-month follow-up than patients receiving surgery only ( p <.05); patients reporting greater trust in storytellers logged 18.6 fewer actions over time ( p =.04). Patients' topical interests evolved, with patients watching more follow-up care and survivorship videos at Exposure3. The intervention was feasible and evaluated favorably. New videos might satisfy patients' changing interests.